RF testing of QPSK device - Chan, Siew Meng. (2008)
The concepts of RF testing of a QPSK device are introduced and followed by the presentation of the simulation results of a common RF tests involving a Quadrature Phase Shift Keying (QPSK) modulator and demodulator.